2017
DOI: 10.1055/s-0036-1588777
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Diverse Natural Products via Dual-Mode Lewis Acid Induced Cascade Cyclization Reactions

Abstract: The σ/π-binding properties of a series of Lewis acids was studied using DFT calculations. The results led to the identification of Zn(II)/In(III) as a suitable dual-mode Lewis acid for use in promoting cascade cyclization reactions. Based on this finding, we developed three new types of dual-mode Lewis acid induced cascade cyclization reactions and have demonstrated the utilities of each process in natural product synthesis.1 Introduction2 Dual-Mode Lewis Acids3 Prins/Conia-Ene Cascade Reaction and its Applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Selective deprotection of the primary TBS ether established the oxygen bridge and gave (±)- 19 , which contains the suitable conformation for selective silyl enol ether formation at C11-12. Thus, ketal (±)- 19 was converted to silyl enol ether followed by carbocyclization with ZnBr 2 , which gave (±)- 20 as a single diastereomer. The structure of (±)- 20 was determined by 2D NMR experiments.…”
Section: Synthesis Of Nl Analogs In Librarymentioning
confidence: 99%
“…Selective deprotection of the primary TBS ether established the oxygen bridge and gave (±)- 19 , which contains the suitable conformation for selective silyl enol ether formation at C11-12. Thus, ketal (±)- 19 was converted to silyl enol ether followed by carbocyclization with ZnBr 2 , which gave (±)- 20 as a single diastereomer. The structure of (±)- 20 was determined by 2D NMR experiments.…”
Section: Synthesis Of Nl Analogs In Librarymentioning
confidence: 99%
“…51–57 After the pioneering studies of Doyle on the RER, this strategy has been successfully employed at the macromolecular level by successive studies of the Yokozawa group 58–62 and the recently published studies by our group. 63–67 Notably, our studies have shown that chlorodimethylsilane (CDMS), which has both reducing agent and Lewis acid characteristics, introduced by Lee and Morandi, 68 is an effective silane compound for obtaining polyethers as well as alkoxy pendant polymers. 63,64 More recently, we showed that when a polymer possessing pendant aldehyde units was subjected to a CDMS-mediated RER using thiols, thioacetal and thioether structures were obtained in the side chain of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…In the RER protocol, carbonyl compounds in the presence of silane and a Brønsted or Lewis acid catalyst afford the synthesis of symmetric and unsymmetrical ethers. 8–28 However, the silyl ether is produced rather than the corresponding ether in the hydrosilylation. Notably, both mechanisms seem to cover the competing reaction pathways.…”
Section: Introductionmentioning
confidence: 99%